Economies of scale and scope in the Danish hospital sector prior to radical restructuring plans - Kristensen, Troels; Olsen, Kim Rose; Kilsmark, Jannie; Lauridsen, Jørgen T.; Pedersen, Kjeld Møller (Health policy (Amsterdam), 2012)
The Danish hospital sector faces a significant rebuilding program driven by recent regional reform and guidelines for acute admission hospitals. Within the next 5–10 years, the number of public hospitals offering acute admission will be reduced from 35 to approximately 20 larger hospitals. As the administrative data may be biased during the middle of a restructuring process our objective was to analyze whether the configuration of Danish public hospitals was subject to economies of scale and scope prior to the restructuring plans. We estimated a quadratic cost function using panel data on the total costs for somatic treatment, casemix adjusted DRG-production values, and other cost drivers for the three years before the 2007 reforms. A short-run cost function was used to derive estimates of a long-run cost function by applying the envelope condition. Next, we estimated economies of scale and scope. We identified moderate-to-significant economies of scale and scope. This indicates that the Danish hospital sector was characterized by unexploited gains from consolidation. Our results suggest that the proposed plans have the potential to result in hospitals that are more efficient. However, post-restructuring studies elsewhere show that the strategy of horizontal integration has failed.